2006
DOI: 10.1080/02701367.2006.10599370
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Muscle Damage After Eccentric Exercise and the Repeated Bout Effect

Abstract: The first purpose of this study was to determine a possible explanation for the variability in the response to eccentric exercise by having participants repeat the same exercise 1 year apart. The second purpose was to examine whether initial injury in response to eccentric exercise was associated with the extent of the repeated bout effect (RBE). Male students performed 30 eccentric contractions (ECC) of the elbow flexors using a dumbbell set at 80% of the pre-exercise maximal isometric force (MIF). Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
1
25
0
1
Order By: Relevance
“…Now it is also well-understood that athletes may be low-, moderate-, and high-respondents to EIMD, a fact that also explains the substantial interindividual variability in the responses seen following various types of exercise protocols used to induce muscle micro-injury 73,108,155,163,168,173175. This phenomenon may be attributed to a number of factors such as age,154,176,177 preconditioning,178180 gender,80,166 genetics,181,182 physical conditioning level,57,183185 and joint range of motion 186.…”
Section: Exercise-induced Inflammation and Sports Performancementioning
confidence: 99%
“…Now it is also well-understood that athletes may be low-, moderate-, and high-respondents to EIMD, a fact that also explains the substantial interindividual variability in the responses seen following various types of exercise protocols used to induce muscle micro-injury 73,108,155,163,168,173175. This phenomenon may be attributed to a number of factors such as age,154,176,177 preconditioning,178180 gender,80,166 genetics,181,182 physical conditioning level,57,183185 and joint range of motion 186.…”
Section: Exercise-induced Inflammation and Sports Performancementioning
confidence: 99%
“…In this context, although it is well known that the muscle force impairment after eccentric exercise differs greatly between subjects, this variability remains poorly understood (Chen 2006). Thus, we can speculate that the variability in fascicle lengthening due to variable tendon contributions and AGR could be involved in the variability in EIMD magnitude.…”
mentioning
confidence: 96%
“…It has been shown that subtle force applications at long muscle lengths can alter a participant's high or low response to the exercise. 7 Because a force-angle curve was not determined during muscle actions in this study, it is possible that "responder" consistency was due to the manner in which participants performed the exercise, as well as the behavioral factors (i.e. the speed of muscle actions during RI30 and RI90 or whether the participants had participated in physical activity in the past) which may partially account for the consistent response in this study.…”
Section: Discussionmentioning
confidence: 86%
“…Conflicting results can be attributed to great interindividual variability on serum CK activity. 7 For example, Machado and Willardson 22 verify differences in serum CK activity following resistance exercise sessions with 1-or 3-min RI lengths when high responder (HR) subjects (i.e. subjects who had a great post-exercise serum CK activity peak) were separated from each group, while the analysis of groups without stratification (i.e.…”
Section: Introductionmentioning
confidence: 99%